Preemptive administration of oral, fast-acting tapentadol compared to tramadol/ketoprofen i.m. to reduce acute pain during and after ESWL procedure in renal stone disease - Vuksanović, Aleksandar; Lađević, Nikola; Jovičić, Jelena; Petrović, Nataša; Jovanović, Vesna; Likić Lađević, Ivana; Lađević, Nebojša; Lazić, Miloš (Medical Research, 2024)
Introduction: Extracorporeal shock wave lithotripsy (ESWL) used to be performed under general anesthesia. Today, although it is a painful procedure, it is performed under analgosedation. The aim of the study is to determine the severity of acute pain associated with ESWL using two comparative protocols for preemptive analgesics: tramadol vs. ketoprofen plus tapentadol. Methods: A clinical, prospective, randomized cohort study included 200 patients of both sexes aged 18-80 years who were divided into two groups: Group I - received a combination of ketoprofen 100 mg/tramadol 50 mg i.m., 30 minutes before surgery; Group II received tapentadol IR 50 mg orally, 1 hour before surgery. Pain intensity (NRS) and complications were recorded before, during and at the end of the procedure. Results: No differences were found in the preoperative characteristics of the patient population and the size and localization of the stone. There was a statistically significant increase in pain intensity before and during surgery in each group, with no difference between groups. In Group II, 14% of patients experienced severe pain during the procedure, compared to 3% in Group I. Nausea was twice as common in patients with severe pain. In the severe pain subgroups of each patient group, nausea occurred in 42% of patients in group II, which was significantly more than 5% in group I (overall incidence in both groups 21%) and all were diagnosed with stone localization. Conclusion: Although both protocols offered an average low pain intensity during the procedure (3.39 vs. 3.85), severe pain and nausea were observed more frequently in the tapentadol group, which could be related to stone localization.